catena-Poly[[bromidocopper(I)]-μ-η(2),σ(1)-3-(2-allyl-2H-tetrazol-5-yl)pyridine] - Wang, Wei (International Union of Crystallography, 2008)
The title compound, [CuBr(C(9)H(9)N(5))](n), has been prepared by the solvothermal treatment of CuBr with 3-(2-allyl-2H-tetrazol-5-yl)pyridine. It is a new homometallic Cu(I) olefin coordination polymer in which the Cu(I) atoms are linked by the 3-(2-allyl-2H-tetrazol-5-yl)pyridine ligands and bonded to one terminal Br atom each. The organic ligand acts as a bidentate ligand connecting two neighboring Cu centers through the N atom of the pyridine ring and the double bond of the allyl group. A three-dimensional structure is formed through weak Cu—Br [3.1579 (8) Å], C—H⋯Br and C—H⋯N interactions.